The collection building and collection management practices of the University of the Philippines Film Center Archives a study - Ilogon, Faye V.; Esquejo, Nemesio A. (Quezon City : Institute of Library Science, University of the Philippines Diliman, 1997)
The undergraduate thesis, The Collection Building and Collection Management Practices of the University of the Philippines Film Center Archives: a Study, is a documentation of the current collection building and collection management policies and practices of the UPFC Archives. It was found that despite the existence of well-planned guidelines, the collection building and collection management operations are affected by factors like the budget, staffing, administrative processes, and the facilities which house the film collection.
Typescript.
Vita.
Thesis (Bachelor of Library Science)--University of the Philippines Diliman pril 1997.
Keywords: Collection development (Libraries) -- Philippines -- Quezon City; Collection management (Libraries) -- Philippines -- Quezon City; University of the Philippines Film Archives